2022
DOI: 10.3389/fimmu.2022.842150
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cytokine Atlas Reveals the Importance of TH2 Polarization and Interferons in Predicting COVID-19 Severity and Survival

Abstract: Although it is now widely accepted that host inflammatory response contributes to COVID-19 immunopathogenesis, the pathways and mechanisms driving disease severity and clinical outcome remain poorly understood. In the effort to identify key soluble mediators that characterize life-threatening COVID-19, we quantified 62 cytokines, chemokines and other factors involved in inflammation and immunity in plasma samples, collected at hospital admission, from 80 hospitalized patients with severe COVID-19 disease who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 42 publications
3
15
0
Order By: Relevance
“…We show that a greater presence of Th2-associated IgG2 and IgG4 (resulting in a smaller skew in IgG subclass imbalance towards Th1-associated IgG1 and IgG3) in the early phase of infection is associated with severe disease, while a stronger skew towards Th1-associated IgG1 and IgG3 may be important in controlling disease progression and clinical recovery. This is supported by data showing that an initial blunted interferon response and heightened T-helper 2 inflammatory response is associated with severe disease ( Baker et al, 2022 ), and is line with other studies ( Roncati et al, 2020 ; Gibellini et al, 2022 ), showing that Th2 polarization, rather than Th1, is predictive of severe disease. A recent study showed that an imbalance between Th1 and Th2 cytokine release was associated with high susceptibility to COVID-19 ( Fahrner et al, 2022 ).…”
Section: Discussionsupporting
confidence: 90%
“…We show that a greater presence of Th2-associated IgG2 and IgG4 (resulting in a smaller skew in IgG subclass imbalance towards Th1-associated IgG1 and IgG3) in the early phase of infection is associated with severe disease, while a stronger skew towards Th1-associated IgG1 and IgG3 may be important in controlling disease progression and clinical recovery. This is supported by data showing that an initial blunted interferon response and heightened T-helper 2 inflammatory response is associated with severe disease ( Baker et al, 2022 ), and is line with other studies ( Roncati et al, 2020 ; Gibellini et al, 2022 ), showing that Th2 polarization, rather than Th1, is predictive of severe disease. A recent study showed that an imbalance between Th1 and Th2 cytokine release was associated with high susceptibility to COVID-19 ( Fahrner et al, 2022 ).…”
Section: Discussionsupporting
confidence: 90%
“…The older person who survived the acute phase may experience an alteration of the immune-inflammatory homeostasis ( Yanes et al, 2017 ). Persistent immune activation may be associated with ongoing symptoms following COVID-19 ( Gibellini et al, 2022 ).…”
Section: Biological Interpretationmentioning
confidence: 99%
“…A number of studies have demonstrated the association between a hyper-inflammatory state, severe disease and mortality from COVID-19. Apart from the most commonly studied inflammatory markers – namely IL-6/CRP, other immune markers which have demonstrated associations with severe COVID-19 include IL-1 family (IL-1β, IL-1RA, IL-18, IL-33) ( 20 ), Th1-related (IL-2, IL-2R, IL-12, IL15, IL-27, TNFα, sTNFR1) ( 21 ), Th2-related (IL-4, IL-5, IL-10, IL-13) ( 22 ) and Th17-related (IL-17A, IL-22) ( 23 ) cytokines, chemokines (IL-8, MCP-1, MCP-3, MIP-1α, MIP-1β, MIP-3β, CXCL9) ( 24 ) interferon-related (IFN-y, IP-10) proteins and growth factors (IL-7, TGF-β, GM-CSF, G-CSF) ( 25 ) - although results are heterogenous and in many cases limited by small sample sizes of clinical cohorts ( 26 29 ). Studies have additionally demonstrated the utility of cytokine ratios (namely IL-6:IL-10) in predicting severe/critical COVID-19 ( 30 ).…”
Section: Introductionmentioning
confidence: 99%